ON FORMS OF PREHISPANIC BURIAL IN KUELAP, AMAZON - Ruiz Estrada, Arturo (2009)
The present paper deals with burial patterns identified in the archaeological complex of Kuelap, in the Luya province, within the Amazonas region, Peru. Such burials represent six categories of funerary repositories among which are mentioned niches, chullpas, underground tombs, sarcophagi and caves. The fact that there are several burial patterns would seem to be linked to the social status of the deceased and to different periods for the site and its history. The shape of the burials and their associated elements indicate they were built between the fifth and fifteenth century A.D. During this time, according to historical data, Kuelap was inhabited by a human group integrated to others in the ancient Luyaychillao province, which at the same time was contemporary to the Chachapoya, Chilcho and other not yet identified groups. Keyword